Habitat associations of grouper (Teleostei: Epinephelidae) assemblages across reefs in the Bidong Archipelago, Malaysia - AMINUDIN MUHAMMAD AFIQ-FIRDAUS; CHE DIN MOHD SAFUAN; MAIZAH M. ABDULLAH; EZMAHAMRUL AFREEN AWALLUDIN; RAHMAN SYAHPUTRA SYAFRUDDIN; MOHMAD FUAD NUR QAMARINA; YUZWAN MOHAMAD; ZAINUDIN BACHOK (Society for Indonesian Biodiversity, 2026)
Abstract. Afiq-Firdaus AM, Safuan CDM, Abdullah MM, Awalludin EA, Syafruddin RS, Qamarina MFN, Mohamad Y, Bachok Z. 2026. Habitat associations of grouper (Teleostei: Epinephelidae) assemblages across reefs in the Bidong Archipelago, Malaysia. Biodiversitas 27 (4): d270426. https://doi.org/10.13057/biodiv/d270426. Groupers (Teleostei: Epinephelidae) are important predatory fishes in coral reef ecosystems, yet their relationships with coral habitat remain insufficiently understood. This study aimed to evaluate grouper assemblages are structured by coral genus composition and benthic habitat, including live coral cover, across reefs in the Bidong Archipelago, Malaysia. Surveys were conducted at 18 stations between March and May 2022 using 100 m belt transects (5×100 m). Grouper assemblages were recorded using Underwater Visual Census (UVC) with video support, while benthic composition and coral genera were assessed using Coral Video Transects (CVT). Data were analyzed using canonical correspondence analysis (CCA), non-metric multidimensional scaling (NMDS), PERMANOVA, and Spearman correlation. A total of 388 individuals representing 11 species were recorded. Assemblages were dominated by Cephalopholis formosa (27%), Cephalopholis boenak (26%), and Cephalopholis cyanostigma (24%). NMDS indicated substantial overlap among sites, suggesting weak spatial structuring of assemblages. Coral genus composition explained 48.9% of constrained variation in CCA but was not statistically significant (p>0.05), consistent with PERMANOVA results (R²: 0.492, p: 0.811). Benthic cover explained 36.0% of variation in CCA and showed a marginal effect in PERMANOVA (R²: 0.434, p: 0.078), with only the “other invertebrates” category showing a significant relationship (p<0.05). Spearman correlation analyses revealed no significant relationships between grouper abundance and habitat variables. Grouper assemblages in the Bidong Archipelago showed weak and largely non-significant associations with coral genus composition and benthic habitat variables, indicating that factors other than measured habitat characteristics may play a greater role in structuring these communities.